PENGARUH PROJECT-BASED LEARNING DAN KOMPETENSI PEDAGOGIK GURU TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD - Anisa Hikmawati, Anisa Hikmawati; Dwi Winarsih; Lusi Rachmiazasi Masduki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this research is to determine the influence of Project-Based Learning and pedagogical competence on the science and science learning outcomes of fifth grade elementary school students. The method used is quantitative research and the data collection method used is the survey one. The results of data analysis regarding Project-Based on science and science learning outcomes for fifth grade elementary school students show a figure of 39.45. This shows that there is a significant influence between Project-Based Learning on the science and science learning outcomes of fifth grade elementary school students. The results of data analysis regarding the influence of pedagogical competence on science and science learning outcomes for fifth grade elementary school students showed a figure of 46.99. This shows that there is a significant influence between pedagogical competence on the science and science learning outcomes of fifth grade elementary school students. There is a relationship between Project-Based Learning and pedagogical competence on the science and science learning outcomes of fifth grade elementary school students. The Project-Based Learning factors and the teacher's pedagogical competence have a positive and very significant influence on the science learning outcomes of elementary school students. The magnitude of the influence on the two independent variables can be seen from R square. It shows the R square value is 0.876 (87.6%), which means that the relationship between Project-Based Learning (X1) and teacher pedagogical competence (X2) simultaneously influence science learning outcomes (Y) by 87.6%. Meanwhile, the remaining 12.4% was influenced by other variables and was not included in this study.